The effect of β-cyclocitral treatment on the carotenoid content of transgenic Marsh grapefruit (Citrus paradisi Macf.) suspension-cultured cells - Zheng, Xiongjie; Zhu, Kaijie; Ye, Junli; Price, Elliott J; Deng, Xiuxin; Fraser, Paul D (Phytochemistry, 2020)
This work reports the development of suspension culture system of transgenic Marsh grapefruit (Citrus paradisi Macf., Rutaceae) callus overexpressing bacterial phytoene synthase; and the use of this suspension culture to investigate the effects of β-cyclocitral on carotenoid content and composition. At a β-cyclocitral concentration of 0.5 mM and after ten days cultivation, analysis of the carotenoids showed a significant increase in the content of β-, α-carotene, and phytoene predominantly. The maximal increase in total provitamin A carotenoids content following β-cyclocitral application was ~2-fold higher than the control, reaching 245.8 μg/g DW. The trend for increased transcript levels of biosynthetic genes PSY and ZDS correlated with the enhancement of the content of these carotenes following β-cyclocitral treatment and GC-MS based metabolite profiling showed significant changes of metabolite levels across intermediary metabolism. These findings suggest that β-cyclocitral can act as a chemical elicitor, to enhance the formation of carotenes in citrus suspension-cultured cells (SCC), which could be utilized in studying the regulation of carotenoid biosynthesis and biotechnological application to the renewable production of nutritional carotenoids.
Keywords: mokřady; Suspension-cultured cells; diterpeny; Carotenoid; Citrus; β-yclocitral; Wetlands; Provitamin A; Aldehydes; Chemical elicitor; aldehydy; grapefruit; kultivované buňky; Diterpenes; Carotenoids; Citrus paradisi; Rutaceae; Cells, Cultured; Citrus paradis; karotenoidy